ENERGY CONSUMPTION AND S AVINGS M ODEL FOR COGENERATION IN C OMMERCIAL B UILDINGS - Nsofor, Emmanuel C. (Distributed Generation & Alternative Energy Journal, 2004)
Environmental problems, electricity deregulation, and anxiety over energy security are contributing to growing attention being paid to co- generation. This study is on the analysis of cogeneration as a conservation strategy for improving energy efficiency in commercial buildings. An en- ergy conservation model for cogeneration that includes applying a sim- plified method and energy data for a commercial establishment was de- veloped. The methodology calculates the current consumption and future operating costs, savings and simple payback for an upgrade system. It was determined that using this strategy would result in significant en- ergy savings with an appreciable payback for the investments made.